PENGARUH SUPERVISI, LINGKUNGAN KERJA DAN KESELAMATAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PADA PTPN V UNIT PKS TANDUN - ,Henni Noviasari, Lisma Trinitatis , Susi Hendriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of supervision, work environment and occupational health and safety on the performance of employees in the processing division at PKS PTPN V Unit Tandun. This research was conducted in Tapung Hulu District, Kampar Regency. The sampling method used is saturated sample technique, where the respondents are 59 people. The data analysis method used in this study is multiple linear regression analysis and uses the SPSS version 25.0 application. The results of this study indicate that supervision affects employee performance at PKS PTPN V Unit Tandun, work environment influences employee performance and occupational health and safety affects employee performance at PKS PTPN V Unit Tandun. From the results of the research conducted, the simultaneous regression test shows that the variables of supervision, work environment and occupational health and safety have a significant influence on the performance of employees in the PTPN V PKS processing unit Tandun. Keywords: Supervision, Work Environment, Occupational Health and Safety, Performance.